Time unit of Mende (Global Journal of Science Frontier Research, 2019)
The concept of time does not up to now have the substantiated physical determination. Contemporary the unit of the measurement of time are based on the periods of the rotation of the Earth around its axis and rotation around the sun, and also the rotation of the Moon around the Earth. This selection of ones is caused both by the historical and practical considerations: by the need for matching human activity with the change of day and night or seasons. In the system SI as the unit of time second, where its following determination is accepted, is accepted: "one second -this is the time interval, equall9192631770 to the periods of the emission, which corresponds to the passage between two hyperfine levels of the basic quantum state of cesium -133 atom at rest with 0 K». In the proposed article it is shown that the unit of time is not primary value, and can be expressed through such fundamental values as mass and length taking into account the fundamental law of the equivalence of gravitational and inert mass.
Keywords: mass; length; force; acceleration; time; second; gravity; time unit of mende